Research involving the Arts in the Graduate Program in Mathematics Education (PPGEM/UNESP) - da Silva, Ricardo Scucuglia Rodrigues [UNESP] (FapUNIFESP (SciELO), 2024)
In this article, we discuss research involving the Arts carried out within the scope of the Graduate Program in Mathematics Education at Sao Paulo State University (PPGEM/UNESP). In the introduction, we state a conception of Arts, recognizing the philosophical problem surrounding the search for such a definition. In section 2, we present a literature review composed of 12 studies defended at PPGEM/UNESP (8 master's theses and 4 doctoral dissertations). These studies are classified into 4 main axes: Ethnomathematics, Geometry, Digital Mathematical Performance (DMP), and Other Perspectives. In section 3, we initially discuss research projects developed by professors at PPGEM/UNESP in which the Arts are the protagonists. Such projects have as their central perspectives the notions of DMP and Aesthetic Mathematical Experience. We specifically address issues in music production. We also discuss studies in which the Arts are explored through issues on digital videos/cinema and/or through emerging aesthetic elements in academic philosophical activity, mainly on the Philosophy of Difference. Based on the studies analyzed, in section 4 we reflect on the role of the Arts in teaching and learning mathematics and in research activity in Mathematics Education. We conclude that, although there are consolidated research trends on Arts in Mathematics Education and the studies developed at PPGEM/UNESP are significant in these consolidations, there is a need to develop more research on this topic, including those that explore other forms/languages, actions and views of the Arts in several school levels and ways of scientific productions.
Pesquisas envolvendo Artes no Programa de Pós-Graduação em Educação Matemática (PPGEM/UNESP)
Keywords: Aesthetic Mathematical Experience; Digital Mathematical Performance; Mathematics Education